Identification of Indian pathogenic races of fusarium oxysporum f. sp ciceris with gene specific, ITS and random markers - Gurjar, Gayatri; Barve, Maneesha; Giri, Ashok P.; Gupta, Vidya (Mycologia, 2009)
In this study we demonstrate the synergistic use of gene-specific markers, ITS-RFLP, ISSR and AFLP for distinguishing Indian F. oxysporum f. sp. ciceris races. We also report for the first time that F. oxysporum f. sp. ciceris race 3, a wilt pathogen of chickpea in India, is actually E proliferatum based on phylogenetic analysis with EF-1 alpha sequence data. E oxysporum f. sp. ciceris races 1, 2 and 4 were easily distinguished from ``race 3'' (F. proliferatum) by PCR amplification with oligonucleotides designed from conserved regions of Hop78 transposon (Hop 78), cutinase (Cut), desaturase (Dst). F oxysporum f. sp. ciceris race 4 was distinguished with the xylanase 3 (xyl3) gene by absence of amplification product only in this race. The Xyl3 amplified-DNA fragment isolated and sequenced from E oxysporum f. sp. ciceris race I was similar to the F-xylanase (Xyl3) gene of E oxysporum f. sp. lycopersici. A TELD motif, which is characteristic of the F-xylanases family, was detected within the deduced amino acid sequence of F. oxysporum f. sp. ciceris. Similarly the F oxysporum f. sp. ciceris Hop78 DNA fragment, which identified ``race 3'' (E proliferatum), was homologous to the Hop78 transposon of E oxysporum f. sp. melonis, including the 100 amino acid conserved domain and the characteristic CCHC motif. The internal transcribed spacer region-restriction fragment length polymorphism (ITS-RFLP) approach along with intersimple sequence repeat (ISSR) method also differentiated ``race 3'' (F. proliferatum). Races 1 and 2 were identified by unique AFLP patterns. Sequence characterization of race-specific AFLP products revealed significant homologies of these sequences with metabolically important genes.
Keywords: AFLP; F. oxysporum f. sp ciceris races; gene specific amplification; ISSR; ITS-RFLP; race delineation; sequence characterization; translation elongation factor (EF-1 alpha)

Biocatalyst development for lactic acid production at acidic pH using inter-generic protoplast fusion - Singhvi, Mamata; Gurjar, Gayatri; Gupta, Vidya; Gokhale, Digambar V. (RSC Advances, 2015)
Global warming and environmental problems force us to develop sustainable processes based on the use of biocatalysts that are eco-friendly with the least potential toxicity. Lactic acid fermentation at neutral pH generates a large amount of gypsum during down-stream processing. Hence it is essential to develop Lactobacillus strains which produce lactic acid at acidic pH thus making the whole downstream process environmentally friendly. Fusant F3 was generated using protoplast fusion between Lactobacillus delbrueckii Mut Uc-3 and Acetobacter pasteurianus NCIM 2314 on solid media at pH 4.0. Fusant F3 was further treated by UV irradiation to generate a mutant, FM1, with improvements in acid tolerance which produced five-fold more lactic acid than the parent strain at acidic pH. The molecular studies using RAPD markers demonstrated that the fusant is derived from both the parental strains, Acetobacter and Lactobacillus and the mutant is derived from the fusant. The utilization of such acid tolerant strains could be able to produce free lactic acid at acidic pH without using neutralizing agents and will offer an effective means for designing environmentally benign processes for lactic acid production.

Identification and functionality prediction of pathogenesis-related protein 1 from legume family - Tellis, Meenakshi; Mathur, Monika; Gurjar, Gayatri; Kadoo, Narendra; Gupta, Vidya (Proteins-Structure Function and Bioinformatics, 2017)
The production and accumulation of pathogenesis-related (PR) proteins in plants is one of the important responses to biotic and abiotic stress. Large number of identified PR proteins has been categorized into 17 functional families based on their structure, phylogenetics, and biological activities. However, they are not widely studied in legume crops. Using 29 PR1 proteins from Arabidopsis thaliana, as query, here we have predicted 92 candidate PR1 proteins through the PSI-BLAST and HMMER programs. These candidate proteins were comprehensively analyzed with, multiple sequence alignment, domain architecture studies, signal peptide, and motif extraction followed by phylogenetic analysis. Further, response of two candidate PR1 proteins from chickpea against Fusarium oxysporum f.sp.ciceri attack was validated using qRT-PCR followed by their 3D structure prediction. To decipher mode of action for PR1s, docking of pathogen extracellular matrix components along with fungal elicitors was performed with two chickpea PR1 proteins. Based on these findings, we propose carbohydrate to be the unique pathogen-recognition feature for PR1 proteins and beta-glucanase activity via beta-glucan binding or modification.

Genome wide analysis of 14-3-3 proteins in Cicer arietinum L. and identification of isoforms responsive to Fusarium oxysporum - Gurjar, Gayatri; Nimbalkar, Suhas; Giri, Ashok; Gupta, Vidya (Current Science, 2021)
In the present study, we have identified and characterized two 14-3-3 isoforms, namely isoform A and C from chickpea (Cicer arietinum L.), that might play a crucial role during disease resistance. Further, in silico analysis of these 14-3-3 proteins was accomplished, including motif identification and structure prediction from deduced amino acid sequences. Expression profiling of the two representative 14-3-3 isoforms in the roots of wilt resistant and susceptible chickpea varieties upon Fusarium oxysporum f. sp ciceri race 1 (FOC1) challenge, revealed time dependent isoform specific differential expression in induced chickpea roots upon FOC1 colonization.
Keywords: Bioinformatics; chickpea 14-3-3s; pathogen responsive; transcriptional analysis